Genetic diversity of emerging hemotropic mycoplasmas in domestic pigs from Brazil - Sonalio, Karina [UNESP]; Perles, Lívia [UNESP]; Gatto, Igor Renan H.; do Amaral, Renan B. [UNESP]; Almeida, Henrique M. S. [UNESP]; Galdeano, José Vanderlei B.; Vieira, Rafael F. C.; André, Marcos R. [UNESP]; de Oliveira, Luis Guilherme [UNESP] (Hindawi, 2020)
Mycoplasma suis and Mycoplasma parvum bind strongly to erythrocytes and may cause clinical hemoplasmosis in swine, affecting several age groups. Mycoplasma spp. infected animals may be asymptomatic carriers and/or show nonspecific clinical signs. In Brazil, information on genetic diversity associated with porcine hemoplasmas (PH) has not been described yet. Therefore, this study has aimed to detect, quantify and characterize the genetic diversity of PH in finishing pigs from technified farms in the state of Goiás, central-western Brazil. Ethylenediaminetetraacetic acid-blood samples from 450 swine belonging to 30 different farms from Goiás state were collected at the slaughterhouse. Quantitative real-time PCR (qPCR) assays were performed for the molecular detection and quantification of PH 16S rRNA gene fragments. Cloning and sequencing of 16S and 23S rRNA amplicons were performed to evaluate the genetic diversity. Moreover, a questionnaire was applied to each farm manager to obtain epidemiological information about the herd. The results on qPCR showed herd occurrence of 68.89% for PH. Quantification values (starting quantity [SQ]) ranged from 8.43 × 10−1 to 4.69 × 106 copies/µl, and 52.71% of the samples presented SQ values equal or lower than 1 × 103 copies/µl. Risk factors were not evaluated once all farms had at least one positive animal. However, Spearman's coefficient test revealed that the occurrence of PH was inversely associated with the number of farrows per week, weaned piglets per week, and weight at slaughter. Phylogenetic analysis based on maximum likelihood and Bayesian methods showed that the 16S rRNA and 23S rRNA gene sequences obtained from five samples formed a single cluster closely related to M. parvum. Genotype analysis using DNASP software confirmed seven and four different 16S and 23S rRNA genotypes among the cloned amplicons, indicating that there are several genotypes of M. parvum circulating in individual pigs and among pig farms in central-western Brazil.
Keywords: emerging disease; genotypes; intensive pig farming; Mycoplasma parvum; Mycoplasma suis; porcine hemoplasmas